The fate of 35S rRNA genes in the allotetraploid grass Brachypodium hybridum. (3rd July 2020) - Borowska‐Zuchowska, Natalia; Kovarik, Ales; Robaszkiewicz, Ewa; Tuna, Metin; Tuna, Gulsemin Savas; Gordon, Sean; Vogel, John P.; Hasterok, Robert
Summary: Nucleolar dominance (ND) consists of the reversible silencing of 35S/45S rDNA loci inherited from one of the ancestors of an allopolyploid. The molecular mechanisms by which one ancestral rDNA set is selected for silencing remain unclear. We applied a combination of molecular (Southern blot hybridization and reverse‐transcription cleaved amplified polymorphic sequence analysis), genomic (analysis of variants) and cytogenetic (fluorescence in situ hybridization) approaches to study the structure, expression and epigenetic landscape of 35S rDNA in an allotetraploid grass that exhibits ND, Brachypodium hybridum (genome composition DDSS), and its putative progenitors, Brachypodium distachyon (DD) and Brachypodium stacei (SS). In progenitor genomes, B .  stacei showed a higher intragenomic heterogeneity of rDNA compared with B .  distachyon . In all studied accessions of B .  hybridum, there was a reduction in the copy number of S homoeologues, which was accompanied by their inactive transcriptional status. The involvement of DNA methylation in CG and CHG contexts in the silencing of the S‐genome rDNA loci was revealed. In the B .  hybridum allotetraploid, ND is stabilized towards the D‐genome units, irrespective of the polyphyletic origin of the species, and does not seem to be influenced by homoeologous 35S rDNA ratios and developmental stage. Significance Statement: Nucleolar dominance (ND) can be present in both hybrids and allopolyploids, and consists of the reversible selective suppression of the 35S rRNA genes that are inherited from one of the ancestral species. We showed that in the allotetraploid Brachypodium hybridum ND is stabilized towards the Brachypodium distachyon ‐like rDNA units, irrespectively of species polyphyletic origin and genetic changes influencing homoeologue 35S rRNA gene ratios.